2022
DOI: 10.3390/sym14071452
|View full text |Cite
|
Sign up to set email alerts
|

Hot Primordial Regions with Anomalous Hydrogenless Chemical Composition

Abstract: We study primordial nucleosynthesis in hypothetical hot regions that could be formed by the primordial density inhomogeneities. It is shown that the regions that survived up to the present times acquire an abnormally high metallicity. This conclusion holds in a wide range of initial parameters of such regions. We considered the thermonuclear reaction rates and estimated abundances of deuterium and helium-3 and -4 inside these areas. It has been established that all baryons tend to form helium-4, which is the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Some hypothetical hot regions that may be formed by primordial density inhomogeneities could be a source of primordial nucleosynthesis; such a process is studied in reference [9]. It is shown that regions that have survived up to the present time acquire an abnormally high metallicity.…”
Section: Contributionsmentioning
confidence: 99%
“…Some hypothetical hot regions that may be formed by primordial density inhomogeneities could be a source of primordial nucleosynthesis; such a process is studied in reference [9]. It is shown that regions that have survived up to the present time acquire an abnormally high metallicity.…”
Section: Contributionsmentioning
confidence: 99%